Analisis Penerapan Total Quality Management Basreng Ikan di UMKM Kripik Riki Kota Cimahi - Hasani, Fiza Jasmine; Junianto (Jurnal Serambi Engineering, 2025)
This study aims to analyse the implementation of Total Quality Management (TQM) in Kripik Riki, a fish-based basreng producer that has been operating since 2006 and has exported to various countries such as Singapore, Taiwan, Mexico, Australia and regularly ships to Malaysia. TQM is one of the modern management concepts that seeks to respond appropriately to any change. The TQM method is a method used in an effort to improve quality, one of which is in Kripik Riki's performance in improving service quality. and synergizing integrated quality management based on the availability of facilities. There are four main pillars of TQM used as the focus of the study, namely: (1) customer focus, (2) continuous quality improvement, (3) total employee involvement, and (4) efficient process management. This study uses a mixed methods approach through interviews, observations and literature review. The results of the study indicate that the implementation of TQM at Kripik Riki has significantly contributed to the improvement of product quality, production efficiency and customer satisfaction, supporting the success of this company in both local and international markets.